Numerical Investigation of CFRP Strengthened Unreinforced Masonry Walls with Openings - Unsal Aslan, Zeynep; Karslioglu, Metin; Doran, Bilge (TAYLOR & FRANCIS LTD, 2026)
Owing to its inhomogeneous nature, masonry shows highly nonlinear behavior. Therefore, it is crucial to develop a numerical model that accurately and practically represents the nonlinear behavior of unreinforced masonry (URM) walls. This article presents a numerical investigation of the in-plane behavior of carbon fiber reinforced polymer (CFRP) strengthened URM walls containing openings subjected to constant axial compression and monotonically increasing lateral loads. For this purpose, a three-dimensional nonlinear finite element analysis was accomplished by ANSYS (R) software at the macro level. The Drucker-Prager plasticity model was employed to define the in-plane behavior of URM walls, while the CFRP strips were defined to behave as a linear elastic orthotropic material. The analysis results confirmed that the presented numerical modeling technique successfully simulated the experimental lateral load-displacement behavior of five specimens under in-plane loading. Furthermore, the model can effectively simulate the experimental deformation and cracking pattern at the global scale, thus providing a practical analysis method for the simulation of URM walls strengthened with CFRP.
Keywords: unreinforced masonry wall; carbon fiber reinforced polymer; opening; macro modeling; Drucker-Prager; BRICK MASONRY; SHEAR BEHAVIOR; INPLANE; PANELS; Construction & Building Technology; Engineering